TEACHERS’ ASSESSMENT LITERACY IN APPLYING PRINCIPLES OF LANGUAGE ASSESSMENT - Diah Wulansari Hudaya (Proceedings Education and Language International Conference, 2017)
Assessment is an essential activity in teaching and learning process. However, most teachers do not feel adequately prepared in assessing their students. Therefore, this study focuses on the investigation of the teachers’ assessment literacy in terms of teachers’ preparation level in assessing students’ performance, teachers’ practices in applying principles of language assessment in their classroom, and the usefulness of the questionnaire developed for them. Forty three in-service teachers were administered 31 items questionnaire that covers principles of language assessment with 1-4 Likert scale, 3 open-ended questions and 7 items of background questionnaire. The quantitative data were analyzed by means of descriptive statistics in terms of percentage, mean, and standard deviation and the qualitative result were summarized, categorized, and analyzed for frequency of mention. The results showed that 79 % teachers felt prepared in assessing students’ performance, it was supported teachers’ practices in applying the principles (88.7 % agree), and 86 % teachers thought that the questionnaire that covers the principles of language assessment was useful for them to evaluate and/ or design a test. Finally, it is recommended that by applying the principles of language assessment in making a good test, teachers will be able to improve their instruction and understand how to use the test to help their students in improving their success in the target language.Keywords: assessment literacy, principles of language assessment, teachers’ practices